Analisis Kewenangan Lembaga Penjamin Simpanan (LPS) dalam Upaya Penjaminan Dana Nasabah - Al-Amanah, Tuhfatul Abrar; Sumardi, Juajir; Famauri, Andi Tenri (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to implement the Authority and Role of the IDIC in Efforts to Guarantee Customer Funds to provide a sense of security for public savings funds in banks. The method of research is qualitative, using interviews and documentation as data collection methods. The results of this study indicate that (1) The authority and role of LPS in guaranteeing public savings in the banking world is to provide a sense of security for customer deposit funds; (2) the occurrence of cases of bank failures, break-ins, and slips of funds that occurred in the banking world. This is a form of violation that is detrimental to the customer, and LPS, in accordance with the applicable laws and regulations, has the authority to guarantee customer deposits at the bank.